2023
DOI: 10.1093/infdis/jiad018
|View full text |Cite
|
Sign up to set email alerts
|

Association of Culturable-Virus Detection and Household Transmission of SARS-CoV-2, California and Tennessee, 2020–2022

Abstract: From two SARS-CoV-2 household transmission studies (enrolling April 2020 – January 2022) with rapid enrollment and specimen collection for 14 days, 61% (43/70) of primary cases had culturable-virus detected ≥6 days post-onset. Risk of secondary infection among household contacts tended to be greater when primary cases had culturable-virus detected after onset. Regardless of duration of culturable-virus, most secondary infections [70% (28/40)] had serial intervals <6 days, suggesting early transmission. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Perhaps this could be attributable to higher viral load in index cases responsible for onward transmission in the household. This is consistent with a household transmission study in the US in A c c e p t e d M a n u s c r i p t which levels of viral culture positivity in index cases were correlated with the risk of infection of in other household members [20].…”
Section: Discussionsupporting
confidence: 90%
“…Perhaps this could be attributable to higher viral load in index cases responsible for onward transmission in the household. This is consistent with a household transmission study in the US in A c c e p t e d M a n u s c r i p t which levels of viral culture positivity in index cases were correlated with the risk of infection of in other household members [20].…”
Section: Discussionsupporting
confidence: 90%
“…While previous studies have demonstrated a relationship between viral culture positivity and SARS‐CoV‐2 transmission, culture status at the time of infection and during illness is not available [ 4 ]. Our findings affirm that certain symptoms can provide information for infectiousness and could be used to guide isolation to mitigate transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies looking at the relationship between SARS‐CoV‐2 viral culture positivity and SARS‐CoV‐2 transmission are scarce. However, within a household setting, we have previously shown that there may be an increased risk of secondary infection among household contacts when primary cases are culture positive for longer than 5 days after illness onset [ 4 ]. Viral culture positivity may be a proxy for infectiousness, underscoring the importance of understanding how symptoms are associated with viral culture positivity.…”
Section: Introductionmentioning
confidence: 99%